The Differences in the Susceptibility Patterns to Triclabendazole Sulfoxide in Field Isolates of Fasciola hepatica Are Associated with Geographic, Seasonal, and Morphometric Variations. - Fernandez-Baca, M.V. (2022)
Triclabendazole (TCBZ) resistance is an emerging problem in fascioliasis that is not well understood. Studies including small numbers of parasites fail to capture the complexity of susceptibility variations between and within Fasciola hepatica populations. As the first step to studying the complex resistant phenotype–genotype associations, we characterized a large sample of adult F. hepatica with diverging TCBZ susceptibility. We collected parasites from naturally infected livestock slaughtered in the Cusco and Cajamarca regions of Peru. These parasites were exposed to TCBZ sulfoxide (TCBZ.SO) in vitro to determine their susceptibility. We used a motility score to determine the parasite’s viability. We titrated drug concentrations and times to detect 20% non-viable (susceptible conditions) or 80% non-viable (resistant conditions) parasites. We exposed 3348 fully motile parasites to susceptible (n = 1565) or resistant (n = 1783) conditions. Three hundred and forty-one (21.8%) were classified as susceptible and 462 (25.9%) were classified as resistant. More resistant parasites were found in Cusco than in Cajamarca (p < 0.001). Resistant parasites varied by slaughterhouse (p < 0.001), month of the year (p = 0.008), fluke length (p = 0.016), and year of collection (p < 0.001). The in vitro susceptibility to TCBZ.SO in wildtype F. hepatica was associated with geography, season, and morphometry.